Analisis Kesulitan Guru Dalam Implementasi Kurikulum Merdeka di SD Negeri 02 Janapria - Yatmi Prihatien; M. Syahruddin Amin; Yul Alfian Hadi (Journal on Education, 2023)
This research aims to determine teachers' difficulties in implementing the Independent Curriculum, factors causing teacher difficulties in implementing the Independent Curriculum and teachers' efforts to overcome difficulties in implementing the Independent Curriculum. This research is qualitative research with a descriptive approach carried out at SD Negeri 02 Janapria. Techniques and instruments for collecting data for this research were carried out by means of observation, interviews and documentation. Based on research results regarding teacher difficulties in implementing the Independent Curriculum at SD Negeri 02 Janapria, there are several difficulties, causal factors and efforts to overcome difficulties, namely: 1). Teachers' difficulties in implementing the Independent Curriculum, namely A). Difficulty in Analyzing Teaching Modules, B). Difficulty compiling question grids, assessment rubrics, differentiating between summative and formative assessments and filling out report cards, C). Less proficient in utilizing technology so they do not use the Technological Pedagogical Content Knowledge (TPACK) learning model, D). Not Using Digital Learning Media, E). Difficulties in Differentiated Learning. 2). Factors Causing Teacher Difficulties Include A). There is no training related to the Independent Curriculum, B). Limited Teacher Abilities. 3). Efforts to overcome these difficulties are A). Establishing Good Communication With Parents, B). Teachers Participate in Teacher Working Groups, C). The Principal Provides Adequate Facilities and Infrastructure Needs.